Practical design calculations for groundwater and soil remediation - Kuo, Jeff. (Boca Raton : CRC, 2014)
"This new edition has updates throughout the text, and it presents all new material on air sparging, dual phase extraction, chemical oxidation, and vacuum pumps, as well as several new practical examples. It illustrates the engineering calculations needed during site assessment and remedial investigations. It also shows readers how to estimate the rates of groundwater movement and plume migration. This book provides important design calculations for vadose zone soil remediation as well as groundwater remediation"--
Includes bibliographical references and index.
Keywords: Groundwater -- Purification